Elucidating the effect of gradient structure on strengthening mechanisms and fatigue behavior of pure titanium. (May 2021) - Li, Xiao; Sun, Bin-Han; Guan, Bo; Jia, Yun-Fei; Gong, Cong-Yang; Zhang, Xian-Cheng; Tu, Shan-Tung
Graphical abstract: Highlights: Grain refinement resulted from deformation twinning, phase transformation, and dislocation slip. The effect of grain refinement, dislocation density, and deformation twinning on strength was analyzed quantitatively. Fatigue-induced grain coarsening sustained the cumulative plastic strain during cyclic deformation. The GNS layer could change the fatigue crack initiation mode. Abstract: Gradient nanostructured (GNS) layer was fabricated on the pure titanium using ultrasonic surface rolling process. With the coaction of deformation twinning, phase transformation, and dislocation slip, a spatial gradient of grain size distribution was formed. Nanocrystalline and amorphous phase exist simultaneously on the top surface. The effect of grain refinement, dislocation density, and deformation twinning on strength was analyzed quantitatively. Stress-controlled fatigue tests showed that enhanced fatigue strength was achieved on the GNS Ti due to the synergetic effect of microstructure and unique mechanical properties. The primary mechanism was fatigue-induced grain coarsening sustained the cumulative plastic strain during cyclic deformation and the GNS layer could change the crack initiation mode.